Behaviour change techniques, intervention features and usability of diet apps - Richard Pavlicek; Kevin A. Cradock (Preventive Medicine Reports)
Objective: Identify the behaviour change techniques and intervention features in popular diet apps. Methods: The most popular diet apps were identified from the top 200 ranked apps in the Health & Fitness sections of the App Store and Google Play in September 2023. Selected apps were used for one week and their content analysed for the presence of behaviour change techniques and intervention features. Apps were rated using the Mobile App Rating Scale score. Results: Thirteen apps with 23 app versions (free & premium) were included. The mean number of behaviour change techniques was 18.3 ± 5.8. The most frequently coded behaviour change techniques were predominantly from the ‘Goals and planning’ and ‘Feedback and monitoring’ categories. Apps contained 21.1 ± 6.1 intervention features and scored a mean Mobile App Rating Scale rating of 3.8 ± 0.3. There was a strong, statistically significant correlation (r = 0.69; p = 0.01) between the number of behaviour change techniques and the Mobile App Rating Scale rating. Analysis identified discrepancies between the Mobile App Rating Scale rating and the App Store and Google Play ranking systems. Conclusions: Selected apps contained a high number of behaviour change techniques and intervention features. Most included apps lacked an evidence base and safety features. App engagement, optimal use of time, safety features and app ranking systems require further research to provide evidence-based recommendations.